Diabetes, Body Fatness, and Insulin Prescription Among Adolescents and Young Adults with Cancer - Holowatyj, Andreana N. (J Adolesc Young Adult Oncol, 2021)
Purpose: Rates of obesity and obesity-related health consequences, including type 2 diabetes (T2D) and cancer, continue to rise. While cancer patients are at an increased risk of developing T2D, the prevalence of T2D and insulin prescription among young patients with cancer remains unknown. Methods: Using the Total Cancer Care Study cohort at Huntsman Cancer Institute (Salt Lake City, UT), we identified individuals age 18–39 years at cancer diagnosis between 2009 and 2019. Multivariable logistic regression was used to investigate associations between body mass index (BMI) with insulin prescription within 1 year of cancer diagnosis. Results: In total, 344 adolescents and young adults (AYAs) were diagnosed with primary invasive cancer. Within this cohort, 19 patients (5.5%) were ever diagnosed with T2D, 48 AYAs ever received an insulin prescription (14.0%), and 197 were overweight or obese (BMI: 25+ kg/m(2)) at cancer diagnosis. Each kg/m(2) unit increase in BMI was associated with 6% increased odds of first insulin prescription within 1 year of cancer diagnosis among AYAs, even after adjustment for age, sex, smoking history, marital status, glucocorticoid prescription, and cancer treatments (odds ratio = 1.06, 95% confidence interval 1.02–1.11; p = 0.005). Conclusion: One in every 18 AYAs with cancer ever had T2D, 1 in 7 AYA patients with cancer ever received an insulin prescription, and higher BMI was associated with increased risk of insulin prescription within a year of cancer diagnosis among AYAs. Understanding the incidence of T2D and insulin prescription/use is critical for short-term and long-term clinical management of AYAs with cancer.